A history of cant and slang dictionaries. Volume IV, 1937-1984 - Coleman, Julie (Oxford : Oxford University Press, 2010)
In the fourth volume of her pioneering history, Julie Coleman considers the trends of lexicographers in a period dominated by the Second World War, the Cold War, various civil rights movements, and numerous youth trends.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English language -- Lexicography -- History; English language -- Early modern, 1500-1700 -- Lexicography; English language -- Slang -- History; Cant -- Great Britain -- History